1999
DOI: 10.1002/(sici)1096-9896(199907)188:3<258::aid-path350>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of losses of heterozygosity and replication errors in primary colorectal carcinomas and corresponding liver metastases

Abstract: In order to investigate genetic alterations specific to liver metastases of colorectal carcinomas, losses of heterozygosity and replication errors have been compared in 15 cases of primary colorectal carcinoma and in the corresponding metastatic liver tumours. Fifteen microsatellite markers located on 13 different chromosomal arms were used in the study. The LOH patterns of the primary and the metastatic tumours were identical in eight cases and showed differences in seven cases. Areas of deletion predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…The region of chromosome 8p21-22 has been identified as a liver metastatic susceptibility locus whose disruption increases metastatic potential (44). Chromosome 8p is also frequently lost in late stage and metastatic CRC (45,46). Given this, it is likely that a reduction in miR-320a expression may also be associated with clinicopathological parameters in primary CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The region of chromosome 8p21-22 has been identified as a liver metastatic susceptibility locus whose disruption increases metastatic potential (44). Chromosome 8p is also frequently lost in late stage and metastatic CRC (45,46). Given this, it is likely that a reduction in miR-320a expression may also be associated with clinicopathological parameters in primary CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have suggested that additional abnormalities can be observed in metastases when compared to primary tumor, 16,17 there is currently a lack of data concerning intermetastatic and intrametastatic variability regarding genetic alterations and chemosensitivity. The aim of our study was to assess intrametastatic and intermetastatic heterogeneity within colorectal liver metastases.…”
mentioning
confidence: 99%
“…12 Interestingly, LOH at 3p25 and 3p23 has been associated with lymph node metastases in squamous-cell carcinoma of the esophagus and with colorectal cancers and poor survival in patients with colorectal carcinoma, respectively. [13][14][15] A second candidate gene on 3p25 is PPAR␥, a member of the nuclear receptor superfamily. This gene is involved in adipocyte differentiation, cholesterol homeostasis, lipogenesis, thermogenesis and glucose homeostasis.…”
mentioning
confidence: 99%